Influence of Yoga on Body Image Satisfaction in Men. Issue 1 (August 2014) - Flaherty, Mary
The aim of this study was to examine the influence of yoga practice on body image satisfaction in men. Male Figure Drawings were used to explore body image satisfaction in yoga beginners ( n = 26, M age = 40.3yr., SD = 11.6), experienced yoga practitioners ( n = 22, M age = 46.4yr., SD = 11.6), and non-yoga practicing aerobic and weight training exercisers ( n = 34, M age = 41.2yr., SD = 11.9). Satisfaction was significantly higher among the yoga groups than the exercisers. There was no statistical difference between the body satisfaction scores of the experienced yoga group and the beginner yoga students. This may suggest that individuals drawn to yoga have greater body satisfaction than exercisers, and that regular yoga practice possibly further increases body satisfaction.